Surface influences on falling film boiling and pool boiling of saturated refrigerants : influences of nanostructures, roughness and material on heat transfer, dryout and critical heat flux of tubes - Meyer, Josua P. (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2020.